TCV mirrors cleaned by plasma. (August 2017) - Marot, L.; Coda, S.; Kajita, S.; Moser, L.; Steiner, R.; Meyer, E.
Highlights: Plasma cleaning of mirrors exposed in TCV was carried out. Reflectivity measurements with a spectrophotometer compared to the simulated reflectivity using a refractive index of 1.5 and a Cauchy model for the aC:D gives good confidence in the estimated film thickness. Recovery of the reflectivity was not complete for the Au mirror mostly due to damage of the surface by tokamak exposure i.e. breakdown phenomena typical for electrical treeing. A fractal dimension of 2 was calculated for these breakdown phenomena which is typical for random motion of arc spot. Abstract: Metallic mirrors exposed in TCV tokamak were cleaned by plasma in laboratory. A gold (Au) mirror was deposited with 185–285 nm of amorphous carbon (aC:D) film coming from the carbon tiles of TCV. Another molybdenum (Mo) mirror had a thicker deposit due to a different location within the tokamak. The thickness measurements were carried out using ellipsometry and the reflectivity measurements performed by spectrophotometry revealed a decrease of the specular reflectivity in the entire range (250–2500 nm) for the Mo mirror and specifically in the visible spectrum for the Au. Comparison of the simulated reflectivity using a refractive index of 1.5 and a Cauchy model for the aC:D gives good confidence on the estimated film thickness. Plasma cleaning using radio frequency directly applied to a metallic plate where the mirrors were fixed demonstrated the ability to remove the carbon deposits. A mixture of 50% hydrogen and 50% helium was used with a −200 V self-bias. Due to the low sputtering yield of He and the low chemical erosion of hydrogen leading to volatile molecules, 20 h of cleaning were needed for Au mirror and more than 60 h for Mo mirror. Recovery of the reflectivity was not complete for the Au mirror most likely due to damage of the surface during tokamak exposure (breakdown phenomena).